Eksplorasi teknik pengolahan sampah masker medis menjadi produk daur ulang - Rostiyanti, Susy Fatena; Condro, Fendya Tristanto; Tjhang, Handi; Yang, Michella Junaidi; Evangelina, Rhema (Institut Seni Indonesia Yogyakarta, 2024)
The Covid-19 pandemic that hit the world in 2019 caused the number of medical masks to be used to increase. The increasing use of masks has led to a high amount of mask waste being used and environmental pollution caused by people who often throw away masks carelessly. Medical masks are made from polypropylene (PP) which is difficult to decompose, so medical mask waste needs to be handled so it doesn't pollute the environment. Among the three basic techniques for treating waste, the recycle technique was chosen. This study uses a meta-analysis method, which involves analysing data obtained from other journals. Of the 6 journals studied, the recycling techniques that are suitable for PP materials and are most often used by Indonesian people are hot press and extrusion. The recycling technique analysis is based on data collected through the Google Scholar website. Through this research, the advantages and disadvantages of hot press and extrusion techniques can be obtained. Both of these techniques produce different forms of plastic, as the hot press technique which produces plastic sheets is more suitable for use in the handicraft recycling process, while extrusions that produce plastic pellets are more suitable for use in large-scale, high-scale recycling processes such as furniture and other interior materials.